Half-Baked High-Resolution Referencing. - Cerf, Vinton G. (Communications of the ACM, 2021)
The author discusses what he terms high-resolution referencing, a kind of digital information preservation involving the referencing of anchor points among uniform resource locators (URLs) within a Web page. The article examines the possibilities of time resolution in document processing systems.